A plan of the sea coast from Gage Point to Cumberland Cape including Dartmouth and Granby Bays with the coal mines in that extent taken from the large survey of the island of Cape Britain survey'd agreable to the orders and instructions of the right honble. the Lords Commissioners of Trade and Plantations / by Samuel Holland esqr surveyor general for the northern district of North America &c. - Holland, Samuel, 1728-1801
Enclosed in: Holland to Gage, July 2, 1767.; Additional information at left of plan: Drawn for his excellency the honble. Major General Thos. Gage commander in chief of his majesty's forces in America &c by Ensn. George Goldfrap of the 60th Regt.; Identifies ruins of Fort William and various outcrops and burning mines of coal.